2016
DOI: 10.7189/jogh.06.020409
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Neisseria meningitidis infections in China: a systematic review and meta–analysis

Abstract: BackgroundNeisseria meningitidis is a leading cause of bacterial meningitis and septicemia in children and young adults worldwide. The disease burden associated with N. meningitidis infections has not been systematically assessed in China. Therefore, we undertook this study to determine the burden of meningococcal disease in China.MethodWe performed a systematic review and meta–analysis of articles on N. meningitidis incidence, carriage, seroprevalence and mortality rates in China by searching the Chinese BioM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Surveillance data indicated that the incidence and prevalence of Nm serogroups continually varies both geographically and temporally [23,24]. Currently, meningococcal serogroup B (MenB) is a major cause of IMD in North America, South America, Australia, North Africa, and Europe, although a decreasing incidence trend is being observed [25], which was supported by the data presented from other countries at the 2018 GMI meeting [10,11,[26][27][28][29][30].…”
Section: Serogroup Distributionmentioning
confidence: 84%
“…Surveillance data indicated that the incidence and prevalence of Nm serogroups continually varies both geographically and temporally [23,24]. Currently, meningococcal serogroup B (MenB) is a major cause of IMD in North America, South America, Australia, North Africa, and Europe, although a decreasing incidence trend is being observed [25], which was supported by the data presented from other countries at the 2018 GMI meeting [10,11,[26][27][28][29][30].…”
Section: Serogroup Distributionmentioning
confidence: 84%
“…9 However, recent subnational estimates indicate an incidence rate of 1.84 cases per 100,000 population, suggesting that the overall incidence rate for China is underestimated. 10 Historically, China has experienced five epidemics of MD between 1938 and 1977. 10,11 The peak incidence of MD was recorded in 1967 with 403 cases per 100,000 population, >3,040,000 recorded cases and >160,000 deaths with a case fatality rate of approximately 5.5%.…”
Section: Review Of the Global Incidence And Epidemiology Of Meningocomentioning
confidence: 99%
“…10 Historically, China has experienced five epidemics of MD between 1938 and 1977. 10,11 The peak incidence of MD was recorded in 1967 with 403 cases per 100,000 population, >3,040,000 recorded cases and >160,000 deaths with a case fatality rate of approximately 5.5%. Following the universal use of serogroup A MD (MenA) polysaccharide vaccines in China in the 1980s and the introduction of MenA polysaccharide vaccines in to the Expanded Programme for Immunization (EPI) in China in 2008, the reported incidence of MD has steadily declined to <0.52 cases per 100,000 population in 2009 12 ; this decline has been particularly evident in the last five years owing to an increasing vaccination coverage rate.…”
Section: Review Of the Global Incidence And Epidemiology Of Meningocomentioning
confidence: 99%
See 2 more Smart Citations